Reallocation of Corporate Resources and Managerial Incentives in Internal Capital Markets - Sandro Brusco; Fausto Panunzi (Center for Economic Studies and ifo Institute (CESifo), 2002)
Diversified firms often trade at a discount with respect to their focused counterparts. The literature has tried to explain the apparent misallocation of resources with lobbying activities or power struggles. We show that diversification can destroy value even when resources are efficiently allocated ex post. When managers derive utility from the funds under their purview, moving funds across divisions may diminish their incentives. The ex ante reduction in managerial incentives can more than offset the increase in firm value due to the ex post efficient reallocation of funds. This effect is robust to the introduction of monetary incentives. We apply our model to the analysis of the optimal reallocation policy and to the effect of the asymmetry among divisions. In general it is optimal for headquarters to commit not to reallocate at least a fraction of funds. As a result, the investment in a given division is more sensitive to the division's cash flow than to other divisions cash flow. Asymmetries in size and growth prospects increase the diversification discount.
Keywords: 330